Pengaruh Rekrutmen dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Tjiwulan Putra Mandiri Kab. Tasikmalaya - Hanna Himatul Fuaddah; Mila Karmila; Arga Sutrisna (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research aims to determine the effect of recruitment and work discipline on the performance of employees of PT. Tjiwulan Putra Mandiri District. Tasikmalaya. The research method used is quantitative, descriptive. The type of data used is primary data and secondary data, with a sample of 70 respondents who are employees of PT. Tjiwulan Putra Mandiri District. Tasikmalaya, and using the saturated sample method. The analytical tool used was SPSS version 25. Data collection techniques used questionnaires and interviews. The results of the study show that Recruitment and Work Discipline simultaneously have a significant effect on Employee Performance. Recruitment is partially positive and significant to Employee Performance. Work Discipline partially has a significant effect on Employee Performance.